Botulinum toxin injections in treatment of post stroke upper extremity spasticity [İnme sonrasi üst ekstremi̇te spasi̇tesi̇ni̇n botuli̇num toksi̇n enjeksi̇yonu i̇le tedavi̇si̇] - (:unkn) unknown (My University, 2001)
Recently, botulinum toxin has been proposed as an effective, safe and selective method of reducing muscle tone. In this study we applied botulinum toxin to the patients with spasticity in their upper extremities due to stroke occured at least 6 months ago. 10 patients (7 male, 3 female) with an average age of 62.7 were included and all have completed the study. The patients were examined at the baseline and 1 week, 2 weeks, 1 month, 2 months, 3 months and 4 months after botulinum toxin injection. Our parameters were spasticity (Ashworth), Barthel, HAQ, Motricity, active and passive ROM of upper extremity joints and patient's global assessment. All the parameters showed statistically significant improvement in the second week. The effect reached to a maximum in the second month. Spasticity which was 2.71 at the baseline, was found 1.92 in 2. month (p<0.01) and 2.31 in 4. month (p<0.01). The other parameters showed a similar progress as well. In the end of fourth month most of the parameters were still significantly better then the preinjection values. No adverse effect was seen. We conclude that botulinum toxin is a safe and well tolerated agent for spasticity.
Keywords: Botulinum toxin; Spasticity; Stroke